PENGGUNAAN WEBSITE SEBAGAI MEDIA PROMOSI HOME INDUSTRY PADA TIM PENGGERAK PKK - Realize Realize; Tukino Tukino (LPPM Universitas Abdurrab, 2019)
Home industry production results are only traditionally managed as promoted by word of mouth, and sometimes rely solely on the number of visitors to the sales place of the product, so the product takes a long time to increase sales volume. Now with capitalize a set of computers or smartphones that have been equipped with the Internet network can be used as a tool or media to publish all activities / promotional activities undertaken by the domestic business actors. In this activity, business activists will be given material about what the website, especially weblog and its benefits, how to make it, and how to use and manage it properly to support and improve the ability in promoting the product. This is not without reason, because almost all citizens who already have a household business is less understand the use of the internet let alone use the Internet media as one of the media to promote household products that they produce. The main target in the implementation of community service activities is to improve the ability of the community in the utilization of the Internet as a powerful medium as a partner of the government in moving the economic factors.